Food applications and ethnomedicinal properties of psyllium: a concise review - Rabia Shabir Ahmad; Farzana Siddique; Ahmed Elawady; Atreyi Pramanik; Fakhar Islam; Ali Imran; Umber Shehzadi; Saima Naz; Ojukwu Moses; Mohd Asif Shah; Abdela Befa Kinki (Cogent Food & Agriculture)
Recently, there has been a significant rise in interest in the application of dietary fiber in health maintenance and illness control. Cardio-metabolic disease has reached pandemic proportions across the world. Dietary fiber consumption can reduce the risk factors related to Cardiometabolic Disorders (CMD). Psyllium, particularly its husk, is a popular dietary fiber supplement that is frequently used to improve cereals and other food items. The effects of psyllium on bile acid absorption, suppression of fatty acid absorption, and modification of glucose metabolism are the processes responsible for its effectiveness. Psyllium also exhibits antioxidant and anti-inflammatory properties, which support its involvement in preventing diabetes-related problems. Psyllium’s capacity to lower uric acid levels increases its potential cardiovascular advantages. This review highlights the psyllium’s nutritional composition, food application, and ethno-medicinal effect in detail.